ChemInform Abstract: One‐Pot Two‐Step Cycloaddition Reaction for Convenient Synthesis of Polycyclic Spirooxindole‐Fused [1, 3]Oxazines. Issue 6 (21st January 2016) - Sun, Jing; Gong, Hui; Yan, Chaoguo
Abstract: The novel spirooxindoline fused [1, 3]oxazines (V) and (VI) are efficiently synthesized by an one‐pot two‐step domino reaction, which involves the sequential formation of a Huisgens 1, 4‐dipole, 1, 4‐dipolar cycloaddition and a Diels—Alder reaction.